Answer

Verified

367.5k+ views

**Hint:**First mention the general quadratic equation and then mention the formula of the roots given by $x = \dfrac{{ - b \pm \sqrt {{b^2} - 4ac} }}{{2a}}$ and substitute the values as per the given equation to get the answer.

**Complete step by step answer:**

We are given that we are required to solve ${x^2} - 11x + 28 = 0$ using the quadratic formula.

The general quadratic equation is given by $a{x^2} + bx + c = 0$, where a, b and c are the real numbers.

The roots of this general quadratic equation is given by the following formula:-

$ \Rightarrow x = \dfrac{{ - b \pm \sqrt {{b^2} - 4ac} }}{{2a}}$

Now, if we compare the given quadratic equation ${x^2} - 11x + 28 = 0$ to the general quadratic equation $a{x^2} + bx + c = 0$, we will then obtain the following:-

$ \Rightarrow $a = 1, b = - 11 and c = 28

Now, putting these values in the formula of quadratics, we will then obtain the following:-

$ \Rightarrow x = \dfrac{{ - ( - 11) \pm \sqrt {{{( - 11)}^2} - 4(1)(28)} }}{{2(1)}}$

Simplifying some calculations in the above equation, we will then obtain the following equation:-

$ \Rightarrow x = \dfrac{{11 \pm \sqrt {121 - 112} }}{2}$

Simplifying the calculations inside the square – root in the above equation, we will then obtain the following equation:-

$ \Rightarrow x = \dfrac{{11 \pm \sqrt 9 }}{2}$

Simplifying the calculations inside the square – root further in the above equation, we will then obtain the following equation:-

$ \Rightarrow x = \dfrac{{11 \pm 3}}{2}$

Therefore, the values of x can be 7 and 4.

**Hence, the roots are 4 and 7.**

**Note:**You can solve the above problem using the below method of splitting the middle term like the following:-

We are given that we are required to solve ${x^2} - 11x + 28 = 0$ using the quadratics formula.

We can write the given equation as:-

$ \Rightarrow {x^2} - 4x - 7x + 28 = 0$

Taking x common from first two terms, we will then obtain the following equation:-

$ \Rightarrow x(x - 4) - 7x + 28 = 0$

Taking – 7 common from first the last two terms, we will then obtain the following equation:-

$ \Rightarrow x(x - 4) - 7(x - 4) = 0$

Now taking (x – 4) common, we will then obtain the following:-

$ \Rightarrow (x - 4)(x - 7) = 0$

Thus the roots are 4 and 7.

Recently Updated Pages

Three beakers labelled as A B and C each containing 25 mL of water were taken A small amount of NaOH anhydrous CuSO4 and NaCl were added to the beakers A B and C respectively It was observed that there was an increase in the temperature of the solutions contained in beakers A and B whereas in case of beaker C the temperature of the solution falls Which one of the following statements isarecorrect i In beakers A and B exothermic process has occurred ii In beakers A and B endothermic process has occurred iii In beaker C exothermic process has occurred iv In beaker C endothermic process has occurred

The branch of science which deals with nature and natural class 10 physics CBSE

The Equation xxx + 2 is Satisfied when x is Equal to Class 10 Maths

Define absolute refractive index of a medium

Find out what do the algal bloom and redtides sign class 10 biology CBSE

Prove that the function fleft x right xn is continuous class 12 maths CBSE

Trending doubts

Difference between Prokaryotic cell and Eukaryotic class 11 biology CBSE

What is BLO What is the full form of BLO class 8 social science CBSE

Difference Between Plant Cell and Animal Cell

Fill the blanks with the suitable prepositions 1 The class 9 english CBSE

Give 10 examples for herbs , shrubs , climbers , creepers

Fill the blanks with proper collective nouns 1 A of class 10 english CBSE

Change the following sentences into negative and interrogative class 10 english CBSE

What is pollution? How many types of pollution? Define it

What organs are located on the left side of your body class 11 biology CBSE